Composite materials science and technology : selected, peer reviewed papers from the 2018 International Conference on Composite Materials Science and Technology (ICCMST 2018), April 6-8, 2018, Bangkok, Thailand - Amemiya, Takashi; Lei, Xuelin; Peng, Xiong Qi (Key engineering materials ;, 2018)
At the International Conference on Composite Materials Science and Technology in 2018 (ICCMST 2018, Bangkok, Thailand, April 6-8, 2018) it was organized the multiple concurrent sessions by experts in the various fields of the modern materials engineering. It facilitated the exchanges of ideas, novel practical techniques, and applications in the field of advanced materials science and technologies, such as composite materials, polymers, ceramics, glass, nanomaterials, chemical technologies, nanotechnologies and powder metallurgy. We hope this collection will be useful for many readers whose activity is related to the modern materials and processing technologies. Polymers, Composites, Ceramics, Glass, Nanomaterials, Synthesis, Processing, Powder Metallurgy Materials Science.